The Use of Personal Protective Equipment to Prevent Work Accidents among Vegetable Farmers in the Tengger Tribe - Afandi, Alfid; Ardiana, Anisah; Rondhianto (International Journal of Community Services, 2024)
Agriculture is the main livelihood for the majority of the population in Indonesia. One is becoming a vegetable farmer in the Tengger tribe community in the highlands of the Bromo mountains, Probolinggo. In the process, this activity carries the risk of causing injury to farmers, such as sharp wounds and exposure to solar radiation. The side effects of this work, if carried out without proper preparation, can cause disease and affect farmers' health. So special precautions are needed to reduce this risk. One activity that can be carried out is to increase awareness of using personal protective equipment to minimize the risk of injury and radiation exposure. This activity was carried out for one day and was packaged as health education carried out in groups by vegetable farmers and accompanied by facilitators. The hope is that this activity can increase farmers' self-awareness in using personal protective equipment when working on mountain slopes to be safer and avoid bad risks due to work. Keywords: Personal Protective Equipment, Health Education, Vegetable Farmers